IMPLEMENTASI UNDANG-UNDANG NOMOR 14 TAHUN 2005 DALAM PENINGKATAN KUALIFIKASI AKADEMIK GURU SD MELALUI PENDIDIKAN TINGGI JARAK JAUH DI WILAYAH KABUPATEN BELITUNG - Aripin, Sofjan; Alton, Latifah (LPPM Universitas Terbuka, 2010)
The policyis afundamental referencefor theimplementer, butpolicy implementationis thedeterminant ofthe policyis successfulorfails. Act(Act) No. 14of 2005, is onereferencein the implementation ofpolicy andacademicqualificationprogramsfor teachersand lecturerstoimprovecompetencein thefield.Governmentthrough the Ministryof NationalEducation, andlocal government asa policyimplementeron the groundthat the2015targetshould bea qualifiedteacherStrata1 (S1). GovernmentDistrictEducation OfficeBelitungupshave targetedthatby 2013allprimary schoolteachers(SD) have already qualifiedS1. Some constraintsin the implementation ofthe programcan not be avoidedbutthese obstaclescan beovercome through thedistance educationcarried outin cooperationwith theUnit ofDistance LearningCoursesOpen University(UPBJJ-UT) Pangkalpinang.